Drug Interaction Studies with Dexlansoprazole Modified Release (TAK-390MR), a Proton Pump Inhibitor with a Dual Delayed-Release Formulation: Results of Four Randomized, Double-Blind, Crossover, Placebo-Controlled, Single-Centre Studies - Vakily, Majid; Lee, Ronald D.; Wu, Jingtao; Gunawardhana, Lhanoo; Mulford, Darcy (Clinical drug investigation, 2009)
Background and objective: Most proton pump inhibitors are extensively metabolized by cytochrome P450 (CYP) isoenzymes, as are many other drugs, giving rise to potential drug-drug interactions. Dexlansoprazole modified release (MR) [TAK-390MR] is a modified-release formulation of dexlansoprazole (TAK-390), an enantiomer of lansoprazole, which employs an innovative Dual Delayed Release™ technology designed to prolong the plasma dexlansoprazole concentration-time profile following once-daily oral administration. As with lansoprazole, dexlansoprazole is metabolized mainly by CYP3A and CYP2C19. Based on in vitro studies, dexlansoprazole has the potential to inhibit activity of these isoenzymes and also may induce human hepatic CYP1A and CYP2C9 activity. To determine whether dexlansoprazole has an effect on these isoenzymes in vivo , drug interaction studies with dexlansoprazole MR were conducted. Methods: Four separate randomized, double-blind, two-way crossover, placebo-controlled, single-centre studies were conducted in healthy volunteers to evaluate the effect of dexlansoprazole on the pharmacokinetics of four test substrates (diazepam, phenytoin, theophylline [administered as intravenous aminophylline] and warfarin), which were selected based on in vitro and/or in vivo data that suggest a potential drug interaction with CYP isoenzymes or potentially coadministered narrow therapeutic index drugs. In each study, dexlansoprazole MR 90 mg or placebo was administered once daily for 9 or 11 days in each period. Subjects received a single dose of test substrate in each study period. Pharmacokinetic parameters of the test substrates were estimated using noncompartmental methods. A conclusion of no effect of dexlansoprazole MR on the test substrate was made if the 90% confidence intervals (CIs) for the ratios of the central values for the observed maximum plasma drug concentration (C max ) and the area under the plasma concentration-time curve (AUC) of test substrate administered with dexlansoprazole MR versus placebo were within 0.80–1.25 based on an analysis of variance model. The potential for a pharmacodynamic interaction was also assessed for warfarin using prothrombin time, measured as the international normalized ratio. Routine safety assessments were conducted in these studies. Results: Mean C max and AUC values were generally similar for each test substrate when administered with multiple once-daily doses of dexlansoprazole MR or placebo. The 90% CIs for the bioavailability of these test substrates administered with dexlansoprazole MR relative to that obtained when the substrates were administered with placebo were within the bioequivalency range of 0.80–1.25, indicating that multiple doses of dexlansoprazole MR had no effect on the pharmacokinetics of these drugs. Additionally, dexlansoprazole MR had no effect on the pharmacodynamics of warfarin. Administration of these drugs with dexlansoprazole MR 90 mg or placebo was well tolerated; the only serious adverse event, which led to a subject’s discontinuation from the study, was considered unrelated to study drugs. Conclusions: Coadministration of dexlansoprazole MR with diazepam, phenytoin or theophylline did not affect the pharmacokinetics of these drugs, and therefore is unlikely to alter the pharmacokinetic profile of other drugs metabolized by CYP2C19, CYP2C9, CYP1A2 and perhaps CYP3A. Additionally, dexlansoprazole MR coadministered with warfarin did not affect the pharmacokinetics of the warfarin enantiomers and had no effect on the anticoagulant activity of warfarin. Dexlansoprazole MR was well tolerated in these trials of healthy subjects.